High-speed copper-clad plate prepared from functional plastic
A copper clad laminate using functional plastics with PEEK powders and nano-fillers addresses high dielectric issues in conventional laminates, offering low loss and constant properties suitable for 5G, with cost-effective mass production.
Patent Information
- Application Number
- CN202411621128.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Conventional copper clad laminates made with epoxy resin adhesives have high dielectric constants and loss factors, exceeding the requirements for 5G high-frequency applications, and their production involves high-temperature processes that are costly and complex, making mass production difficult.
A high-speed copper clad laminate is prepared using functional plastics, comprising functional plastic-modified epoxy-based prepregs with PEEK powders, nano-sized boron nitride, titanium nitride, and hollow glass microspheres, which are processed at lower temperatures to achieve low dielectric loss and constant properties, suitable for 5G applications.
The laminate exhibits low dielectric loss and constant, excellent heat resistance, and can be produced at lower costs with simpler processes, facilitating industrial mass production and meeting the performance requirements of 5G high-frequency substrates.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a high-speed copper clad laminate prepared using functional plastics. Background Art
[0002] With the rapid development of 5G technology, the requirements for high frequency, lightweight and dielectric loss performance of electronic components are getting higher and higher. As an important component of electronic components, high-speed copper clad laminates determine the industrial technology level of electronic components.
[0003] The existing high-speed copper clad laminate preparation process is as follows: epoxy resin adhesive is coated on the upper and lower surfaces of electronic grade glass cloth and thermally cured to form a semi-cured substrate for copper clad laminate, multiple semi-cured substrates are stacked on each other to form a copper clad laminate substrate, and then copper foil is coated on one or both sides of the copper clad laminate substrate and hot-pressed to obtain a high-speed copper clad laminate.
[0004] At present, the dielectric constant D of copper clad laminates prepared with conventional epoxy resin adhesives is k (3.5~5.5), dielectric loss factor D f (>0.010) is too high. Copper clad laminates made of epoxy resin adhesive are suitable for conventional circuit substrates, but cannot meet the needs of today's high-frequency circuit substrate copper clad laminate composite materials.
[0005] The performance requirements of 5G high-frequency copper-clad laminate materials are as follows: Dielectric constant D k Less than 4, dielectric loss factor D f Less than 0.008.
[0006] In order to meet the material performance requirements of 5G high-frequency copper clad laminates, the prior art uses polytetrafluoroethylene resin with low dielectric loss factor combined with high dielectric performance fillers to make copper clad laminates. Although it meets the material performance requirements of 5G high-frequency copper clad laminates, it cannot be industrially mass-produced. The specific problem of the above-mentioned prior art is that polytetrafluoroethylene-based copper clad laminates need to be pressed and formed at a high temperature of 380-400°C, which has high equipment requirements and complex processes, resulting in high overall production costs. To this end, the applicant provides a high-speed copper clad laminate made of functional plastics with low dielectric loss and low dielectric constant. Summary of the invention
[0007] The problem to be solved by the present invention is to provide a high-speed copper-clad laminate prepared by using functional plastics, wherein the high-speed copper-clad laminate prepared by using functional plastics has low dielectric loss D f The advantages can meet the needs of the current effect market and the future development of copper clad laminate materials. The dielectric constant D k Less than 4, dielectric loss factor D f Less than 0.008.
[0008] The present invention provides a high-speed copper-clad laminate made of functional plastic, which is realized by the following technical solutions: A high-speed copper-clad laminate prepared using functional plastics is formed by hot-pressing and curing a plurality of functional plastic-modified epoxy-based prepregs; the functional plastic-modified epoxy-based prepregs are made of electronic-grade glass cloth and functional plastic-modified epoxy resin; the functional plastic-modified epoxy resin comprises 5-20 parts by weight of functional plastic particles, 100 parts by weight of epoxy resin, 8-25 parts by weight of a curing agent composition, 5-25 parts by weight of a functional filler composition, 60-150 parts by weight of an organic solvent, and 1-5 parts by weight of a functional auxiliary agent; The functional plastic particles are PEEK powders, and the particle size of the PEEK powders is less than 25 microns; The mass ratio of the total mass of the functional plastic and the functional filler composition to the mass ratio of the epoxy resin (15-25): 100; The functional filler composition includes at least one of nano-sized boron nitride, titanium nitride, silicon dioxide, and submicron-sized hollow glass microspheres; the organic solvent is at least one of toluene, xylene, acetone, butanone, N,N-dimethylformamide, DMF, and propylene glycol monomethyl ether; and the functional additive includes at least one of a defoamer, a leveling agent, and an anti-aging agent.
[0009] The epoxy resin reacts with the surface carboxyl-activated PEEK powder to generate a functional plastic modified epoxy-based semi-cured sheet with an island structure. The PEEK powder has good heat resistance stability and low dielectric loss performance, thereby giving the prepared high-speed copper clad laminate good heat resistance and dielectric properties. At the same time, the specific functional filler composition is assisted to improve the overall insulation and heat dissipation of the high-speed copper clad laminate, which can meet the dielectric performance requirements and dimensional stability and creep resistance requirements of the 5G high-frequency PCB substrate. In summary, the high-speed copper clad laminate in the present invention has low dielectric loss and excellent heat resistance, which meets the dielectric performance requirements of the 5G high-frequency PCB board.
[0010] Preferably, the functional filler composition is nano-sized boron nitride, titanium nitride, silicon dioxide, or submicron-sized hollow glass microspheres.
[0011] With the addition of the main filler - nano-sized boron nitride, the copper clad laminate CCL in the present application gives the present application good low dielectric loss factor and low dielectric constant performance; in addition, nano-sized boron nitride has a low thermal expansion coefficient, high thermal conductivity and insulation, and good thermal stability and chemical resistance, thereby also giving the present application good heat-resistant performance, chemical corrosion resistance, good processing performance and relatively good insulation and heat dissipation performance. Good insulation and heat dissipation performance can assist heat-resistant performance, avoid long-term high-temperature load aging and failure of the copper clad laminate CCL, and is beneficial to the improvement of the overall service life and stability of the copper clad laminate CCL.
[0012] Adding a small amount of auxiliary filler - nano titanium nitride particles in this application can block the gaps between the resin molecular chains, thereby improving the density, barrier properties, wear resistance and impact resistance of the copper clad laminate. The high-density copper clad laminate CCL structure is conducive to further improving the dielectric constant and dielectric loss factor. Nano titanium nitride can further assist in improving the dielectric properties of the copper clad laminate CCL.
[0013] In this application, a small amount of auxiliary filler - nano-silicon dioxide is added. There are a large number of unsaturated residual bonds and hydroxyl groups in different bonding states on the surface. The epoxy resin composition has high compatibility and is easy to cross-link with its polymer chain segments, which is used to improve the density of the copper-clad laminate CCL and improve the dielectric constant and dielectric loss factor. In addition, the copper-clad laminate CCL prepared by adding nano-silicon dioxide has good weather resistance, mainly because the reflectivity of nano-silicon dioxide to ultraviolet short waves 200~280nm is 70%~80%; the reflectivity to ultraviolet medium and long waves 280~400nm is 80%~85%; the reflectivity to visible light 400~800nm is more than 85%; the reflectivity to near-infrared rays in the 800~1350 band is also more than 70%.
[0014] Adding auxiliary filler-hollow glass microspheres in this application can reduce the total weight of copper clad laminate CCL and achieve the purpose of lightweight. The main component of hollow glass microspheres is silicon dioxide, and there are many unsaturated residual bonds and hydroxyl groups in different bonding states on its surface. It has high compatibility with special fluorosilicone modified epoxy resin and is easy to cross-link with its polymer chain segments. It can improve the density of copper clad laminate CCL, improve dielectric constant and dielectric loss factor, and also has good ultraviolet light, visible light, and infrared light reflection performance, which can improve the overall weather resistance.
[0015] Preferably, the preparation method of the functional plastic particles is as follows: Step 1: freeze the PEEK resin pellets with liquid nitrogen and place them in a low-temperature pulverizer for pre-crushing. The particle size of the obtained pre-crushed material is less than 1 mm. The obtained pre-crushed material is input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; Step 2: The PEEK crushed material obtained in step 1 is transferred to a fine classifier for classification and particle size screening to obtain a PEEK fine crushed material with a particle size of less than 25 microns; Step three, the PEEK fine crushed material obtained in step two is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:(0.5-2), the treatment temperature is 0-4°C, and the low-temperature plasma treatment is performed for 300-500s to obtain a finished PEEK crushed material with surface activation of active functional groups, that is, the target product functional plastic particles.
[0016] Preferably, in the step three, the finished PEEK crushed material is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:2, the treatment temperature is 0°C, and the low-temperature plasma treatment is performed for 8 minutes to obtain the finished PEEK crushed material with surface activation of active functional groups, that is, the target product functional plastic particles.
[0017] The surface of the finished PEEK crushed material has active carboxyl functional groups that can react with epoxy resin, which solves the problem of precipitation of the finished PEEK crushed material caused by the compatibility of the finished PEEK crushed material with epoxy resin, and effectively improves the service life of the high-speed copper clad laminate.
[0018] Preferably, in the step 2, the PEEK crushed material obtained in the step 1 is transferred to a micro-classifier for classification and particle size screening to obtain a PEEK fine crushed material with a particle size of less than 25 microns, and the obtained PEEK fine crushed material with a particle size of less than 25 microns and an ethanol aqueous solution are put into a planetary ball mill in a mass ratio of 1: (5-10), the volume ratio of deionized water to ethanol in the ethanol aqueous solution is 1: (0.2-1.0), zirconium oxide is used as grinding beads, and wet ball milling is performed at 400-600rpm for 15-30min to obtain the PEEK fine crushed material.
[0019] The finished PEEK crushed material has a smaller particle size after high-speed ball milling, which can play a nano effect, further improve the dielectric properties, mechanical strength, and impact toughness of the high-speed copper clad laminate, which is beneficial to improving the market competitiveness of the high-speed copper clad laminate.
[0020] Preferably, the epoxy resin includes at least fluorine-silicon modified epoxy resin and bisphenol A epoxy resin, and the fluorine-silicon modified epoxy resin includes pentafluorophenyl methacrylate, methacryloxysilane KH570, and naphthalene ring type epoxy resin.
[0021] Preferably, the curing agent composition is composed of at least one of pentafluoropropionic anhydride and phthalic anhydride, polyamide resin, and double NCO-terminated polyurethane prepolymer.
[0022] Preferably, the polyamide resin in the curing agent composition is at least one of three-arm polyethylene glycol valerate (amide bond), three-arm polyethylene glycol succinimide carbonate, and two-arm polyethylene glycol succinimide carbonate.
[0023] Preferably, the end-capping isocyanate in the di-NCO-terminated polyurethane prepolymer comprises 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0024] The fluorine and silicon elements introduced into the epoxy resin can effectively reduce the dielectric properties, high temperature resistance and chemical corrosion resistance of the matrix resin itself. Adjusting the benzene ring content (i.e., the π-π conjugated double bond content) in the epoxy resin composition has a positive effect on the dielectric properties of the formed matrix resin cured product. However, it will inevitably lead to a decrease in the impact strength and toughness of the matrix resin cured product, which is not conducive to the processing and use of high-speed copper clad laminates. Therefore, it is necessary to perform high-speed ball milling and refinement treatment on the finished PEEK crushed material to improve the overall impact strength and toughness through the nano effect of the refined PEEK micropowder, or use nano-scale main filler-nano-scale boron nitride with auxiliary filler for toughening and reinforcement treatment to prepare a high-speed copper clad laminate with good dielectric properties, processing performance, high temperature resistance, chemical corrosion resistance and relatively good impact toughness.
[0025] In order to solve the impact strength and toughness problems of high-speed copper clad laminates, polyamide resin is compounded in the curing agent composition. Its use as an elastomer molecular linking block and compounded with inorganic fillers can effectively improve the impact strength and toughness of the matrix resin cured product, and can also help improve the temperature resistance stability and dielectric properties.
[0026] The double NCO-terminated polyurethane prepolymer in the curing agent composition gives the copper clad laminate a low-temperature resistance, making it suitable for use in extreme weather applications, thereby improving the overall safety factor of the copper clad laminate CCL and enhancing the market competitiveness of the product.
[0027] The introduction of fluorine-containing curing agent in the composite curing agent is mainly to adjust the fluorine content in the matrix resin cured product to ensure the dielectric properties and chemical corrosion resistance of the prepared copper clad laminate CCL.
[0028] In summary, the copper clad laminate prepared in the present application has the advantages of low dielectric loss, low dielectric constant and light weight.
[0029] Preferably, the method for preparing the high-speed copper clad laminate made of functional plastic is as follows: Step A, preparation of functional plastic particles; Step B, after the batching kettle is replaced with nitrogen, the accurately measured functional plastic particles, epoxy resin, curing agent composition, functional filler composition, organic solvent, and functional additive are put into the batching kettle for defoaming and mixing treatment, and the batching kettle temperature is 0-10°C, the kettle pressure is 0.06-0.08MPa, and the defoaming and mixing are carried out at 200-400rpm for 3-5min, the kettle pressure is adjusted to 0.04-0.05MPa, and the defoaming and mixing are carried out at 200-400rpm for 10-15min, the kettle pressure is maintained at 0.04-0.05MPa, and the defoaming and mixing are carried out at 500-600rpm for 5-10min, and the functional plastic modified epoxy resin with a solid content of 40-60wt% can be obtained; Step C, preparation of functional plastic modified epoxy prepreg: coating the functional plastic modified epoxy resin prepared in step B on the surface of electronic grade glass cloth, and baking at 140-160° C. for 10-15 minutes; Step D, preparation of high-speed copper clad laminate: take 4-12 functional plastic modified epoxy prepregs prepared in step C, stack the functional plastic modified epoxy prepregs on each other to form a high-speed copper clad laminate substrate, attach a HVLP copper foil on both sides of the high-speed copper clad laminate substrate, then perform hot pressing curing and molding treatment, and naturally cool to obtain a finished high-speed copper clad laminate.
[0030] Preferably, in step D, the preparation of a high-speed copper clad laminate is as follows: 4-12 functional plastic modified epoxy prepregs prepared in step C are taken, the functional plastic modified epoxy prepregs are stacked together to form a high-speed copper clad laminate substrate, a HVLP copper foil is attached to both sides of the high-speed copper clad laminate substrate, and then hot pressing and curing are performed. The hot pressing and curing process parameters are as follows: the head end pressure is 1.5-1.8MPa, the hot pressing plate temperature is 175-190°C, and the hot pressing time is 15-30m. in; the middle end pressure is 2.4-2.6MPa, the hot pressing plate temperature is 200-220℃, and the hot pressing time is 60-120min; the terminal pressure is 3.2-3.5MPa, the hot pressing plate temperature is 220-235℃, and the hot pressing time is 15-30min; after completing the terminal hot pressing treatment, the hot pressing pressure is adjusted to 0.1-0.2MPa, the hot pressing plate temperature is 120-125℃, and the hot pressing time is 30-60min. After taking it out and cooling it naturally to room temperature, the finished high-speed copper clad laminate can be obtained.
[0031] The preparation method provided by the present invention is highly similar to the production equipment adopted in the existing process scheme for preparing copper clad laminates using epoxy resin adhesives, that is, the conventional production line of conventional circuit substrates can meet the production of high-speed copper clad laminates in the present invention. The preparation method of the present invention is relatively simpler than the polytetrafluoroethylene-based copper clad laminates, and the difficulty of implementing the operation is similar to that of the existing process for preparing copper clad laminates CCL using epoxy resin adhesives. The overall production difficulty is relatively low, which is convenient for realizing industrialized mass production and manufacturing, reducing the overall production cost of copper clad laminates, and facilitating the promotion and application of high-quality copper clad laminates.
[0032] In summary, the present invention has the following advantages: 1. The high-speed copper clad laminate in the invention has low dielectric loss and excellent heat resistance, meeting the dielectric performance requirements of 5G high-frequency substrates.
[0033] 2. The preparation method provided by the present invention has a relatively low overall production difficulty, is easy to realize industrialized mass production, reduces the overall production cost of copper clad laminates, and is convenient for the promotion and application of high-quality copper clad laminates. DETAILED DESCRIPTION
[0034] In order to further understand the present invention, the technical scheme of the present invention is clearly and completely explained below in combination with embodiments and comparative examples.
[0035] A high-speed copper-clad laminate made of functional plastic is formed by hot-pressing and curing a plurality of functional plastic-modified epoxy-based prepregs, which are made of electronic-grade glass cloth and functional plastic-modified epoxy resin.
[0036] The functional plastic modified epoxy resin comprises 5-20 parts by weight of functional plastic particles, 100 parts by weight of epoxy resin, 8-25 parts by weight of curing agent composition, 5-25 parts by weight of functional filler composition, 60-150 parts by weight of organic solvent and 1-5 parts by weight of functional auxiliary agent.
[0037] The epoxy resin at least includes fluorine-silicon modified epoxy resin and bisphenol A type epoxy resin. The fluorine-silicon modified epoxy resin includes pentafluorophenyl methacrylate, methacryloxysilane KH570, and naphthalene ring type epoxy resin.
[0038] The curing agent composition is composed of at least one of pentafluoropropionic anhydride, phthalic anhydride, polyamide resin and double NCO-terminated polyurethane prepolymer.
[0039] Preferably, the curing agent composition is pentafluoropropionic anhydride, phthalic anhydride, polyamide resin, and a polyurethane prepolymer terminated with double NCO.
[0040] The polyamide resin in the curing agent composition is at least one of three-arm polyethylene glycol valerate (amide bond), three-arm polyethylene glycol succinimide carbonate, and two-arm polyethylene glycol succinimide carbonate.
[0041] The end-capping isocyanate in the double NCO-terminated polyurethane prepolymer includes 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0042] The mass ratio of the total mass of the functional plastic and the functional filler composition to the mass ratio of the epoxy resin (15-25):100.
[0043] The functional filler composition includes at least one of nano-sized boron nitride, titanium nitride, silicon dioxide, and submicron hollow glass microspheres. Preferably, the functional filler composition is nano-sized boron nitride, titanium nitride, silicon dioxide, and submicron hollow glass microspheres.
[0044] The organic solvent is at least one of toluene, xylene, acetone, butanone, N,N-dimethylformamide, DMF, and propylene glycol monomethyl ether.
[0045] The functional additives include at least one of a defoaming agent, a leveling agent and an anti-aging agent.
[0046] Preferably, the functional additives are composed of defoaming agents, leveling agents and anti-aging agents.
[0047] The functional plastic particles are PEEK micropowders. Preferably, the particle size of the PEEK micropowders is less than 25 microns.
[0048] The preparation method of functional plastic particles is as follows: Step 1: freeze the PEEK resin pellets with liquid nitrogen and place them in a low-temperature pulverizer for pre-crushing. The particle size of the obtained pre-crushed material is less than 1 mm. The obtained pre-crushed material is input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; Step 2: The PEEK crushed material obtained in step 1 is transferred to a fine classifier for classification and particle size screening to obtain a PEEK fine crushed material with a particle size of less than 25 microns; Step three, the PEEK fine crushed material with a particle size less than 25 microns obtained in step two is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:(0.5-2), the treatment temperature is 0-4°C, and the low-temperature plasma treatment is performed for 300-500s to obtain a finished PEEK crushed material with surface activation of active functional groups, that is, functional plastic particles.
[0049] Preferably, in step three, the finished PEEK crushed material is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:2, the treatment temperature is 0°C, and the low-temperature plasma treatment is performed for 8 minutes to obtain the finished PEEK crushed material with surface activation of active functional groups, that is, the target product functional plastic particles.
[0050] Further preferably, in step two, the PEEK fine crushed material with a particle size of less than 25 microns obtained in step two is transferred to a micro-classifying machine for classification and particle size screening to obtain PEEK fine crushed material with a particle size of less than 25 microns, and the PEEK fine crushed material with a particle size of less than 25 microns and an ethanol aqueous solution are put into a planetary ball mill in a mass ratio of 1: (5-10), the volume ratio of deionized water to ethanol in the ethanol aqueous solution is 1: (0.2-1.0), zirconium oxide is used as grinding beads, and wet ball milling is carried out at 400-600rpm for 15-30min to obtain PEEK fine crushed material.
[0051] The preparation method of high-speed copper clad laminate made of functional plastic is as follows: Step A, preparation of functional plastic particles; Step B, after the batching kettle is replaced with nitrogen, the accurately measured functional plastic particles, epoxy resin, curing agent composition, functional filler composition, organic solvent, and functional additive are put into the batching kettle for defoaming and mixing treatment, and the batching kettle temperature is 0-10°C, the kettle pressure is 0.06-0.08MPa, and the defoaming and mixing are carried out at 200-400rpm for 3-5min, the kettle pressure is adjusted to 0.04-0.05MPa, and the defoaming and mixing are carried out at 200-400rpm for 10-15min, the kettle pressure is maintained at 0.04-0.05MPa, and the defoaming and mixing are carried out at 500-600rpm for 5-10min, and the functional plastic modified epoxy resin with a solid content of 40-60wt% can be obtained; Step C, preparation of functional plastic modified epoxy prepreg: coating the functional plastic modified epoxy resin prepared in step B on the surface of electronic grade glass cloth, and baking at 140-160° C. for 10-15 minutes; Step D, preparation of high-speed copper clad laminate: take 4-12 functional plastic modified epoxy prepregs prepared in step C, stack the functional plastic modified epoxy prepregs on each other to form a high-speed copper clad laminate substrate, attach a HVLP copper foil on both sides of the high-speed copper clad laminate substrate, then perform hot pressing curing and molding treatment, and naturally cool to obtain a finished high-speed copper clad laminate.
[0052] Preferably, step D, preparation of high-speed copper clad laminate: take 4-12 functional plastic modified epoxy prepregs prepared in step C, stack the functional plastic modified epoxy prepregs on each other to form a high-speed copper clad laminate substrate, attach a HVLP copper foil on both sides of the high-speed copper clad laminate substrate, and then perform hot pressing curing and molding. The hot pressing curing and molding process parameters are as follows: the head end pressure is 1.5-1.8MPa, the hot pressing plate temperature is 175-190°C, and the hot pressing time is 15-30min. The middle end pressure is 2.4-2.6MPa, the hot pressing plate temperature is 200-220℃, and the hot pressing time is 60-120min; the terminal pressure is 3.2-3.5MPa, the hot pressing plate temperature is 220-235℃, and the hot pressing time is 15-30min; after completing the terminal hot pressing treatment, the hot pressing pressure is adjusted to 0.1-0.2MPa, the hot pressing plate temperature is 120-125℃, and the hot pressing time is 30-60min. After taking it out and cooling it naturally to room temperature, the finished high-speed copper clad laminate can be obtained.
[0053] Embodiment 1 A method for preparing a high-speed copper-clad laminate using functional plastics in this embodiment comprises the following steps: Step 1, preparation of functional plastic modified epoxy resin; S1.1, preparation of fluorosilicone modified epoxy resin: 0.1 mol of γ-methacryloxypropyltrimethoxysilane (KH570), 0.1 mol of pentafluorophenyl methacrylate (CAS NO.: 13642-97-2), and 80 g of xylene were added to a four-necked beaker equipped with a thermometer, a stirring device, a reflux condenser, and a dropping funnel, heated to 80°C and kept warm for 10 min, 0.25 g of AIBN catalyst was added dropwise to the reaction system through a dropping funnel every 30 min, the reaction temperature was maintained at 85°C, the reaction was carried out under nitrogen protection for 100 min, and then cooled to 30°C to obtain a fluorosilicone intermediate; the obtained fluorosilicone intermediate was mixed evenly with 320 g of EBA-65 naphthalene ring epoxy resin (CAS: 27610-48-6), 240 g of toluene, and 150 g of butanone at 180 rpm, and 1.0 g of methyl ethyl ketone was added to the four-necked beaker. The DMP-30 catalyst was heated to 108°C for ring-opening reaction for 30 minutes, and then cooled to room temperature to obtain fluorosilicone modified epoxy resin (fluorosilicone modified EBA-65 is a naphthalene ring type epoxy resin); At the same time, prepare isocyanate-terminated polyurethane prepolymer: first prepare polyol: put 1 mol of 2,6-diamino-3,5-difluoropyridine (CAS NO.: 247069-27-8), 1 mol of terephthalic acid, and 2.061 mol of 3-methyl-1,5-pentanediol into a reactor, stir and mix evenly at 240 rpm, then heat to 135°C at 0.6°C / min and keep warm for 3h, then heat to 230°C at a uniform rate of 0.5°C / min and keep warm for 200min, then control the top temperature of the distillation tower at 102±0.5°C, take samples to measure the acid value as the reaction proceeds, and when the test acid value reaches 30±2 mgKOH / g, add 120 ppm of tetrabutyl titanate and evacuate, that is, the mass of tetrabutyl titanate is 12*10 of the total mass of 2,6-diamino-3,5-difluoropyridine, terephthalic acid, and 3-methyl-1,5-pentanediol. -3wt%, and gradually pump the pressure in the autoclave from normal pressure to relative vacuum -0.098MPa (25torr, the set vacuum degree of the vacuum pump equipment) within 4h, and then take samples for testing. When the hydroxyl value of the product in the autoclave reaches 112±3mgKOH / g, the product is qualified. The reactor is broken by nitrogen and cooled to 110℃, and the material is unloaded and packaged to obtain a fluorinated polyol with a number average molecular weight of 1000; then 0.2 mol of the fluorinated polyol prepared in S1.1, 0.3 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 (BASF PolyTHF 2000), 1.2 mol of dicyclohexylmethane diisocyanate HMDI (Yantai Wanhua), 0.05 mol of 4-(hexafluoro-2-hydroxyisopropyl)aniline (CAS NO.:722-92-9), 0.85 mol of 1,4-butanediol and 0.1 mol of 1,4-butenediol (CAS No.:110-64-5) were added to the reaction kettle and mixed evenly. The mixture was heated to 80°C and reacted until the viscosity of the liquid in the test kettle reached 5000~10000 mPa*s / 25°C. The actual viscosity of the liquid was 6540 Pa*s / 25℃, add 0.6 mol of 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (CAS.: 20649-91-6) for end-capping reaction for 10 min, and mix evenly to obtain a 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione end-capped polyurethane prepolymer; Boron nitride nanosheets, boron nitride whiskers, nano-titanium nitride, nano-silicon dioxide, and hollow glass microspheres were all wet-milled with KH570 coupling agent for 1 h, and the mass ratio of KH570 coupling agent to the above inorganic fillers (boron nitride nanosheets, boron nitride whiskers, nano-titanium nitride, nano-silicon dioxide, and hollow glass microspheres) was controlled at 1:19; At the same time, functional plastic particles are prepared, and the specific method is as follows: First, the PEEK resin pellets (PEEK Junhua 5600G) were frozen with liquid nitrogen and then placed in a low-temperature pulverizer for pre-crushing. The obtained pre-crushed material was screened with a 1mm mesh screen. The particle size of the obtained pre-crushed material was less than 1mm. The obtained pre-crushed material was input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; then it was transferred to a fine-fine grading machine for grading and particle size screening to obtain PEEK fine crushed material with a particle size of less than 25 microns; finally, the obtained PEEK fine crushed material was subjected to low-temperature plasma treatment, the treatment atmosphere was an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas was 1:1, the treatment temperature was 0°C, and the low-temperature plasma treatment was performed for 480s to obtain a finished PEEK crushed material with active functional groups on the surface activated, that is, the target product functional plastic particles; S1.2, after the batching kettle is replaced with nitrogen, weigh 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin (DIC, CAS: 2386-87-0, epoxy equivalent: 128-140, viscosity: 200mPas), 35 parts of bisphenol A type epoxy resin E20 (Baling Petrochemical E20 epoxy resin cyd011, CAS: 38891-59-7), 5 parts of fluorosilicone modified EBA-65 naphthalene ring type epoxy resin prepared in S1.1, and 0.5 parts of 5-trifluoromethyluracil (CAS NO.:54-20-6), 7.5 parts of the isocyanate-terminated polyurethane prepolymer prepared in S1.1 (i.e., 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione-terminated polyurethane prepolymer), 2 parts of three-arm polyethylene glycol valerate (amide bond) with a peak molecular weight Mp of 2000 (3-arm PEG-SGA, Xiamen Sinobond), 3 parts of boron nitride nanosheets (hBN-500nm boron nitride nanosheets, Yamei Nanotechnology), 1 part of boron nitride whiskers (Beijing Dekedaojin Technology, diameter: 1um length: 10-20um), 1 part of nano titanium nitride (Wuhan Huaxiang Kejie Biotechnology, average particle size 700nm), 2 parts of nano silicon dioxide (CAS No. 68611-44-9, AEROSIL R972), 5 parts of hollow glass microspheres (US 3M hollow glass microspheres S15), 8 parts of finished PEEK crushed materials with active functional groups in S1.1 activated on the surface, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001, 3 parts of leveling agent - BYK RHEOBYK R 605 are put into the batching kettle for defoaming and mixing treatment, and the batching kettle temperature is 4±0.5℃, the kettle pressure is 0.08MPa and the defoaming and mixing are carried out at 200rpm for 5min, the kettle pressure is adjusted to 0.05MPa and the defoaming and mixing are carried out at 400rpm for 15min, the kettle pressure is maintained at 0.04MPa and the defoaming and mixing are carried out at 600rpm for 10min, and the functional plastic modified epoxy resin can be obtained; Step 2, preparation of functional plastic modified epoxy prepreg: coating the functional plastic modified epoxy resin on the surface of 2116 electronic grade glass cloth, and baking at 150° C. for 10 minutes to obtain a prepreg; Step 3, preparation of high-speed copper clad laminate: take 8 sheets of the above-mentioned functional plastic modified epoxy semi-cured sheets, superimpose the functional plastic modified epoxy semi-cured sheets on each other to form a high-speed copper clad laminate substrate, attach a piece of HVLP copper foil on both sides of the high-speed copper clad laminate substrate, and then perform hot pressing curing and molding treatment. The hot pressing curing and molding process parameters are as follows: the first end pressure is 1.6MPa, the hot pressing plate temperature is 180°C, and the hot pressing time is 30min; the middle end pressure is 2.5MPa, the hot pressing plate temperature is 215°C, and the hot pressing time is 100min; the end pressure is 3.25MPa, the hot pressing plate temperature is 225°C, and the hot pressing time is 20min; after completing the end hot pressing treatment, adjust the hot pressing pressure to 0.15MPa, the hot pressing plate temperature is 120°C, and the hot pressing time is 60min, and naturally cool to obtain the finished high-speed copper clad laminate.
[0054] Embodiment 2 This embodiment is basically the same as the first embodiment, except that: S1.2, after the batching kettle is replaced with nitrogen, weigh 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepared in S1.1 Prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 3 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 2 parts of nano silicon dioxide, 5 parts of hollow glass microspheres S15, 8 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0055] Embodiment 3 This embodiment is basically the same as the first embodiment, except that: S1.2, after the batching kettle is replaced with nitrogen, weigh 55 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 25 parts of bisphenol A epoxy resin E20, 20 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepared in S1.1 Prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 3 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 2 parts of nano silicon dioxide, 5 parts of hollow glass microspheres S15, 8 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0056] Embodiment 4 This embodiment is basically the same as the second embodiment, except that: S1.2, after the batching kettle is replaced with nitrogen, weigh 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepared in S1.1 Prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 3 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 2 parts of nano silicon dioxide, 5 parts of hollow glass microspheres S15, 5 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0057] Embodiment 5 This embodiment is basically the same as the second embodiment, except that: S1.2, after the batching kettle is replaced with nitrogen, weigh 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepared in S1.1 Prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 3 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 2 parts of nano silicon dioxide, 5 parts of hollow glass microspheres S15, 12 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0058] Embodiment 6 This embodiment is basically the same as the second embodiment, except that: S1.2, after the batching kettle is replaced with nitrogen, 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepreg prepared in S1.1 are weighed. Polymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 1 part of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 1 part of nano silicon dioxide, 11 parts of hollow glass microspheres S15, 10 parts of finished PEEK crushed materials with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0059] Embodiment 7 This embodiment is basically the same as the second embodiment, except that the functional plastic particles are prepared by the following specific method: First, the PEEK resin pellets (PEEK Junhua 5600G) were frozen with liquid nitrogen and then placed in a low-temperature pulverizer for pre-crushing. The obtained pre-crushed material was sieved with a 1mm mesh sieve, and the particle size of the obtained pre-crushed material was less than 1mm. The obtained pre-crushed material was input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; then it was transferred to a fine classifier for classification and particle size screening to obtain PEEK fine crushed material with a particle size of less than 25 microns; finally, the obtained PEEK fine crushed material was subjected to low-temperature plasma treatment, the treatment atmosphere was an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas was 1:2, the treatment temperature was 0°C, and the low-temperature plasma treatment was performed for 480s to obtain the finished PEEK crushed material with active functional groups activated on the surface, that is, the target product functional plastic particles.
[0060] Embodiment 8 This embodiment is basically the same as the second embodiment, except that the functional plastic particles are prepared by the following specific method: First, the PEEK resin pellets (PEEK Junhua 5600G) were frozen with liquid nitrogen and then placed in a low-temperature pulverizer for pre-crushing. The obtained pre-crushed material was screened with a 1mm mesh screen. The particle size of the obtained pre-crushed material was less than 1mm. The obtained pre-crushed material was input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; then it was transferred to a micro-classifier for classification and particle size screening to obtain PEEK fine crushed material with a particle size of less than 25 microns. The PEEK fine crushed material and ethanol aqueous solution were put into a planetary ball mill at a mass ratio of 1: (5-10). The volume ratio of deionized water to ethanol in the ethanol aqueous solution is 1:0.4, zirconium oxide is used as grinding beads, and wet ball milling is performed at 480rpm for 20min to obtain PEEK fine crushed material; finally, the obtained PEEK fine crushed material is subjected to low-temperature plasma treatment, the treatment atmosphere is O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:2, the treatment temperature is 0°C, and the low-temperature plasma treatment is performed for 480s to obtain the finished PEEK crushed material with active functional groups on the surface activated, that is, the target product functional plastic particles.
[0061] Comparative Example 1: The preparation of the functional plastic modified epoxy resin in this comparative example is basically the same as that in Example 1, except that step 1 is different, and the rest are the same.
[0062] Step 1, preparation of the binder resin composition: after the batching kettle is replaced with nitrogen, 60 parts by mass of HP-7200H dicyclopentadiene phenol epoxy resin, 40 parts by mass of bisphenol A epoxy resin E20, 4 parts by mass of dicyandiamide (CAS No. 461-58-5), 6 parts by mass of 2-ethyl-4-methylimidazole (CAS.No: 931-36-2), 12 parts by mass of aluminum hydroxide (HT-205 ultrafine aluminum hydroxide, CAS.No: 21645-51-2, Shandong Taixing New Materials), 8 parts by mass of 800 mesh magnesium hydroxide (CAS.No: 1309-42-8), 20 parts by mass of acetone, 80 parts by mass of xylene, 12 parts by mass of butanone, 2 parts by mass of defoamer-BASF Efka PB 2001, and 3 parts by mass of leveling agent-BYK RHEOBYK R 605 was put into the batching kettle for defoaming and mixing. When the batching kettle temperature was 4±0.5℃ and the kettle pressure was 0.08MPa, the defoaming and mixing were carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing were carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing were carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0063] Comparative Example 2: This comparative example is basically the same as comparative example 1, except that: Step 1, preparation of the binder resin composition: after the batching kettle is replaced with nitrogen, weigh 60 parts by mass of HP-7200H dicyclopentadiene phenol epoxy resin, 40 parts by mass of bisphenol A epoxy resin E20, 4 parts by mass of dicyandiamide (CAS No. 461-58-5), 6 parts by mass of 2-ethyl-4-methylimidazole (CAS.No: 931-36-2), 20 parts of the finished PEEK crushed material with surface activation of the active functional groups in S1.1, 20 parts by mass of acetone, 80 parts by mass of xylene, 12 parts by mass of butanone, 2 parts by mass of defoamer-BASF Efka PB 2001, and 3 parts by mass of leveling agent-BYK RHEOBYK R 605 was put into the batching kettle for defoaming and mixing. When the batching kettle temperature was 4±0.5℃ and the kettle pressure was 0.08MPa, the defoaming and mixing were carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing were carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing were carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0064] Comparative Example 3: The preparation of the binder resin composition in this comparative example is basically the same as that in Example 1, except that: Step 1, preparation of the binder resin composition: after the batching kettle is replaced with nitrogen, weigh 60 parts by mass of HP-7200H dicyclopentadiene phenol epoxy resin, 40 parts by mass of bisphenol A epoxy resin E20, 4 parts by mass of dicyandiamide (CAS No. 461-58-5), 6 parts by mass of 2-ethyl-4-methylimidazole (CAS.No: 931-36-2), 6 parts by mass of boron nitride nanosheets, 2 parts of boron nitride whiskers, 2 parts of nano titanium nitride, 2 parts of nano silicon dioxide, 8 parts of hollow glass microspheres S15, 20 parts by mass of acetone, 80 parts by mass of xylene, 12 parts by mass of butanone, 2 parts by mass of defoamer-BASF Efka PB 2001, and 3 parts by mass of leveling agent-BYKRHEOBYK R 605 was put into the batching kettle for defoaming and mixing. When the batching kettle temperature was 4±0.5℃ and the kettle pressure was 0.08MPa, the defoaming and mixing were carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing were carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing were carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0065] Comparative Example 4: This comparative example is basically the same as comparative example 1, except that: S1.2, after the batching kettle is replaced with nitrogen, 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate-terminated polyurethane prepared in S1.1 are weighed. Prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 2 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 1 part of nano silicon dioxide, 1 part of hollow glass microspheres S15, 5 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min to obtain the functional plastic modified epoxy resin.
[0066] Comparative Example 5: The preparation of the binder resin composition in this comparative example is basically the same as that in Example 1, except that: S1.2, after the batching kettle is replaced with nitrogen, 60 parts by weight of HP-7200H dicyclopentadiene phenol epoxy resin, 30 parts of bisphenol A epoxy resin E20, 10 parts of fluorosilicone modified EBA-65 naphthalene ring epoxy resin prepared in S1.1, 0.5 parts of 5-trifluoromethyluracil, 7.5 parts of isocyanate prepared in S1.1 are weighed. End-capped polyurethane prepolymer, 2 parts of three-arm polyethylene glycol valerate with a peak molecular weight Mp of 2000, 3 parts of boron nitride nanosheets, 1 part of boron nitride whiskers, 1 part of nano titanium nitride, 1 part of nano silicon dioxide, 4 parts of hollow glass microspheres S15, 20 parts of finished PEEK crushed material with surface activation of active functional groups in S1.1, 20 parts of acetone, 80 parts of xylene, 12 parts of butanone, 2 parts of defoamer - BASF Efka PB 2001 and 3 parts of leveling agent-BYK RHEOBYK R 605 were put into the batching kettle for defoaming and mixing. The temperature of the batching kettle was 4±0.5℃, the kettle pressure was 0.08MPa, and the defoaming and mixing was carried out at 200rpm for 5min. The kettle pressure was adjusted to 0.05MPa and the defoaming and mixing was carried out at 400rpm for 15min. The kettle pressure was maintained at 0.04MPa and the defoaming and mixing was carried out at 600rpm for 10min. Functional plastic modified epoxy resin can be obtained. Although the prepared copper clad laminate has excellent dielectric properties, the production cost is high and the toughness is relatively poor.
[0067] Comparative Example 6: The preparation of the binder resin composition in this comparative example is basically the same as that in Example 1, except that: Step 3, preparation of a high-speed copper clad laminate: take 8 functional plastic modified epoxy prepregs prepared in Step 3, superimpose the functional plastic modified epoxy prepregs on each other to form a high-speed copper clad laminate substrate, attach a piece of HVLP copper foil on both sides of the high-speed copper clad laminate substrate, and then perform hot pressing curing molding treatment at a pressure of 2.4 MPa, a hot pressing plate temperature of 200°C, and a hot pressing time of 180 min, and naturally cool to obtain a finished high-speed copper clad laminate.
[0068] Comparative Example 7: The preparation of the binder resin composition in this comparative example is basically the same as that in Example 1, except that: the functional plastic particles are prepared by the following specific method: first, PEEK resin pellets (PEEK Junhua 5600G) are frozen with liquid nitrogen and then placed in a low-temperature pulverizer for pre-crushing treatment, the obtained pre-crushed material is sieved with a 1mm mesh sieve, and the particle size of the obtained pre-crushed material is less than 1mm. The obtained pre-crushed material is input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; finally, it is transferred to a fine classifier for classification and particle size screening treatment to obtain PEEK fine crushed material with a particle size of less than 25 microns.
[0069] Comparative Example 8: The preparation of the binder resin composition in this comparative example is basically the same as that in Example 1, except that: the functional plastic particles are prepared by the following specific method: first, the PEEK resin pellets (PEEK Junhua 5600G) are frozen with liquid nitrogen and then placed in a low-temperature pulverizer for pre-crushing treatment, the obtained pre-crushed material is sieved with a 1mm mesh sieve, the particle size of the obtained pre-crushed material is less than 1mm, and the obtained pre-crushed material is input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; finally, it is transferred to a fine classifier for classification and particle size screening treatment to obtain PEEK fine crushed material with a particle size of 30-40 microns; finally, the obtained PEEK fine crushed material is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:1, the treatment temperature is 0°C, and the low-temperature plasma treatment is performed for 480s to obtain a finished PEEK crushed material with surface activation of active functional groups, i.e., the target product functional plastic particles.
[0070] The high-speed copper-clad laminates obtained in the above examples and comparative examples were subjected to performance tests. The results are shown in Table 1.
[0071] Table 1: Test parameters of copper clad laminate
[0072]
[0073] Note: Performance test: 1. Tg test method: Determined according to IPC TM-650 2.4.25 (DSC). 2. Dielectric constant and dielectric loss factor test method: Determined according to IPC TM-650 2.5.5.5 (10GHz), test conditions C-24 / 23 / 50. 3. Thermal expansion coefficient test method: Determined according to IPC TM-650 2.4.24. 4. Peel strength test method: Determined according to IPC TM-650 2.4.8, test conditions 288 ℃ / 10s.
[0074] Combining Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1, it can be seen that compared with Comparative Example 1, Examples 1 to 3 show that the copper clad laminate prepared by the epoxy resin composition formed by the dicyclopentadiene epoxy resin, the bisphenol A epoxy resin and the prepared fluorosilicone modified epoxy resin has relatively better comprehensive performance.
[0075] Combining Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1, it can be seen that compared with Comparative Example 1, Examples 1 to 3 have relatively better comprehensive performance than the copper clad laminate prepared by the composite curing agent composed of pentafluoropropionic anhydride, isocyanate-terminated polyurethane prepolymer and polyamide resin.
[0076] In addition, the IZOD notched impact strength in Example 1 is 16.95 J / M, the IZOD notched impact strength in Example 1 is 18.38 J / M, while the IZOD notched impact strength in Comparative Example 1 is 13.51 J / M, and the IZOD notched impact strength in Comparative Example 2 is 9.07 J / M. It can be seen that the copper clad laminate prepared under the formula of this application combined with the specific preparation process has relatively good impact toughness, which is convenient for overall processing and production. And the ball milling and nano-processing of PEEK micropowder is conducive to the improvement of the mechanical strength and impact toughness of the high-speed copper clad laminate.
[0077] It can be seen from Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1 that the copper clad laminate prepared with the functional filler composition composed of nano-sized boron nitride, titanium nitride, silicon dioxide, and submicron-sized hollow glass microspheres has relatively better comprehensive performance.
[0078] Combining Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1, it can be seen that the mass ratio of the total mass of the functional plastic and the functional filler composition to the mass ratio of the epoxy resin is (15-25): 100, and the comprehensive performance of the prepared copper clad laminate is relatively good.
[0079] It can be seen from Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1 that surface activation of the finished PEEK crushed material can effectively improve the physical and chemical properties of the copper clad laminate, that is, the surface activation of the PEEK crushed material is necessary, and active carboxyl functional groups are formed on the surface that can react with the epoxy resin, which solves the problem of precipitation of the finished PEEK crushed material due to the compatibility of the finished PEEK crushed material with the epoxy resin, and effectively improves the service life of the high-speed copper clad laminate.
[0080] It can be seen from Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1 that the copper clad laminate prepared by the three-stage hot pressing method provided in the present invention has relatively better comprehensive performance.
[0081] It can be seen from Examples 1 to 8 and Comparative Examples 1 to 8 and Table 1 that the copper clad laminate prepared from PEEK powder with a particle size of less than 25 μm has relatively better comprehensive performance.
Claims
1. A high-speed copper-clad laminate made of functional plastic, characterized in that: The high-speed copper-clad laminate prepared using functional plastic is formed by hot-pressing and curing a plurality of functional plastic-modified epoxy-based prepregs; the functional plastic-modified epoxy-based prepregs are made of electronic-grade glass cloth and functional plastic-modified epoxy resin; the functional plastic-modified epoxy resin comprises 5-20 parts by weight of functional plastic particles, 100 parts by weight of epoxy resin, 8-25 parts by weight of a curing agent composition, 5-25 parts by weight of a functional filler composition, 60-150 parts by weight of an organic solvent, and 1-5 parts by weight of a functional auxiliary agent; The functional plastic particles are PEEK powders, and the particle size of the PEEK powders is less than 25 microns; The mass ratio of the total mass of the functional plastic and the functional filler composition to the mass ratio of the epoxy resin (15-25): 100; The functional filler composition includes at least one of nano-sized boron nitride, titanium nitride, silicon dioxide, and submicron-sized hollow glass microspheres; the organic solvent is at least one of toluene, xylene, acetone, butanone, N,N-dimethylformamide, DMF, and propylene glycol monomethyl ether; and the functional additive includes at least one of a defoamer, a leveling agent, and an anti-aging agent.
2. The high-speed copper-clad laminate made of functional plastic according to claim 1, characterized in that: The preparation method of the functional plastic particles is as follows: Step 1: freeze the PEEK resin pellets with liquid nitrogen and place them in a low-temperature pulverizer for pre-crushing. The particle size of the obtained pre-crushed material is less than 1 mm. The obtained pre-crushed material is input into a disc-type air flow mill for air flow grinding to obtain PEEK crushed material; Step 2: The PEEK crushed material obtained in step 1 is transferred to a fine classifier for classification and particle size screening to obtain a PEEK fine crushed material with a particle size of less than 25 microns; Step three, the PEEK fine crushed material with a particle size less than 25 microns obtained in step two is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:(0.5-2), the treatment temperature is 0-4°C, and the low-temperature plasma treatment is performed for 300-500s to obtain a finished PEEK crushed material with surface activation of active functional groups, that is, functional plastic particles.
3. The high-speed copper-clad laminate made of functional plastic according to claim 2, characterized in that: In the step three, the finished PEEK crushed material is subjected to low-temperature plasma treatment, the treatment atmosphere is an O2 / O3 mixed gas, the volume of O2 and O3 in the O2 / O3 mixed gas is 1:2, the treatment temperature is 0°C, and the low-temperature plasma treatment is performed for 8 minutes to obtain the finished PEEK crushed material with active functional groups activated on the surface, that is, functional plastic particles.
4. A high-speed copper-clad laminate made of functional plastic according to claim 2 or 3, characterized in that: Step 2: The PEEK crushed material obtained in step 1 is transferred to a micro-classifier for classification and particle size screening to obtain a PEEK fine crushed material with a particle size of less than 25 microns. The obtained PEEK fine crushed material with a particle size of less than 25 microns and an ethanol aqueous solution are put into a planetary ball mill at a mass ratio of 1: (5-10), the volume ratio of deionized water to ethanol in the ethanol aqueous solution is 1: (0.2-1.0), zirconium oxide is used as a grinding bead, and wet ball milling is performed at 400-600rpm for 15-30min to obtain the PEEK fine crushed material.
5. The high-speed copper-clad laminate made of functional plastic according to claim 1, characterized in that: The epoxy resin at least includes fluorine-silicon modified epoxy resin and bisphenol A epoxy resin, and the fluorine-silicon modified epoxy resin includes pentafluorophenyl methacrylate, methacryloxysilane KH570, and naphthalene ring epoxy resin.
6. The high-speed copper-clad laminate made of functional plastic according to claim 1, characterized in that: The curing agent composition is composed of at least one of pentafluoropropionic anhydride, phthalic anhydride, polyamide resin, and double NCO-terminated polyurethane prepolymer.
7. The high-speed copper-clad laminate made of functional plastic according to claim 6, characterized in that: The polyamide resin in the curing agent composition is at least one of three-arm polyethylene glycol valerate (amide bond), three-arm polyethylene glycol succinimide carbonate, and two-arm polyethylene glycol succinimide carbonate.
8. The high-speed copper-clad laminate made of functional plastic according to claim 6, characterized in that: The end-blocking isocyanate in the double NCO-terminated polyurethane prepolymer includes 1,3,5-tris(3-isocyanato-4-methylphenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
9. The high-speed copper-clad laminate made of functional plastic according to claim 1, characterized in that: The preparation method of the high-speed copper-clad laminate prepared using functional plastic is as follows: Step A, preparation of functional plastic particles; Step B, after the batching kettle is replaced with nitrogen, the accurately measured functional plastic particles, epoxy resin, curing agent composition, functional filler composition, organic solvent, and functional additive are put into the batching kettle for defoaming and mixing treatment, and the batching kettle temperature is 0-10°C, the kettle pressure is 0.06-0.08MPa, and the defoaming and mixing are carried out at 200-400rpm for 3-5min, the kettle pressure is adjusted to 0.04-0.05MPa, and the defoaming and mixing are carried out at 200-400rpm for 10-15min, the kettle pressure is maintained at 0.04-0.05MPa, and the defoaming and mixing are carried out at 500-600rpm for 5-10min, and the functional plastic modified epoxy resin with a solid content of 40-60wt% can be obtained; Step C, preparation of functional plastic modified epoxy prepreg: coating the functional plastic modified epoxy resin prepared in step B on the surface of electronic grade glass cloth, and baking at 140-160° C. for 10-15 minutes; Step D, preparation of high-speed copper clad laminate: take 4-12 functional plastic modified epoxy prepregs prepared in step C, stack the functional plastic modified epoxy prepregs on each other to form a high-speed copper clad laminate substrate, attach a HVLP copper foil on both sides of the high-speed copper clad laminate substrate, then perform hot pressing curing and molding treatment, and naturally cool to obtain a finished high-speed copper clad laminate.
10. The high-speed copper-clad laminate made of functional plastic according to claim 9, characterized in that: The step D, preparation of high-speed copper clad laminate: take 4-12 functional plastic modified epoxy prepregs prepared in step C, stack the functional plastic modified epoxy prepregs together to form a high-speed copper clad laminate substrate, attach a HVLP copper foil on both sides of the high-speed copper clad laminate substrate, and then perform hot pressing curing and molding. The hot pressing curing and molding process parameters are as follows: the head end pressure is 1.5-1.8MPa, the hot pressing plate temperature is 175-190°C, and the hot pressing time is 15-30min The middle end pressure is 2.4-2.6MPa, the hot pressing plate temperature is 200-220℃, and the hot pressing time is 60-120min; the terminal pressure is 3.2-3.5MPa, the hot pressing plate temperature is 220-235℃, and the hot pressing time is 15-30min; after completing the terminal hot pressing treatment, the hot pressing pressure is adjusted to 0.1-0.2MPa, the hot pressing plate temperature is 120-125℃, and the hot pressing time is 30-60min. After taking it out and cooling it naturally to room temperature, the finished high-speed copper clad laminate can be obtained.
Citation Information
Patent Citations
Method for preparing GF / PEEK (glass fibre / polyether-ether-ketone) composite from modified glass fiber
CN103073841A
Packing contained polyaryl ether ketone composite material, sheet and circuit board containing same
CN106928650A
Halogen-free high-Tg copper-clad substrate and preparation method thereof
CN113667276A
Resin composition and manufacturing method of high-Tg and low-Dk / Df high-frequency copper-clad plate
CN115028963A
Preparation formula and preparation method of peek plastic plate
CN117050461A
Cited By
Composite ultrathin bonding sheet for multi-layer lamination of high-frequency copper-clad plate and preparation method of composite ultrathin bonding sheet
CN119979092A
Copper-clad plate with high binding power and manufacturing method thereof
CN120059400A
